Bulk FDTD Simulation of Distributed Corona Effects and Overvoltage Profiles for HSIL Transmission Line Design - Jon T. Leman; Robert G. Olsen (Energies, 2020)
Power system load growth and transmission corridor constraints are driving industry activity in the area of high surge impedance loading (HSIL). Examples include compact structure design and uprating existing transmission lines. Recent research relating electric field uniformity to transmission line capacity and critical flashover voltage underscored the need for better overvoltage data to quantify insulation margins for HSIL design. To that end, this work extends the finite difference time domain (FDTD) method with distributed corona losses to transmission lines with bundled conductors. The model was adapted for practical use in high-volume statistical transient simulation and applied to an example 500 kV line. Transients included line energization and trapped charge reclosing. Overvoltage profiles and statistical distributions were generated from 9500 simulations obtained by random breaker close timing and variation in line length and altitude. Distributed corona losses reduced 98th percentile line-to-ground switching overvoltages by 4%–14% of nominal. The estimated line-to-ground switching surge flashover probability was 54%–80% lower with corona loss. Corona had less impact on line-to-line overvoltages, but the effects were still notable. Results highlight the importance of considering detailed overvoltage profiles and accounting for corona loss attenuation when seeking to carefully quantify insulation design margins.